DIALLEL ANALYSIS OF RESISTANCE TO BACTERIAL STALK ROT (Pectobacterium chrysanthemi pv. zeae Burk., McFad. and Dim.) IN CORN (Zea mays L.) - Nuning A. Subekti; Artemio M. Salazar (Indonesian Journal of Agricultural Science, 2007)
One of the major disease problems affecting maize farming in the Philippines is bacterial stalk rot (BSR) caused by Pectobacterium chrysanthemi pv. zeae Burk., McFad. and Dim., which is formerly known as Erwinia chrysanthemi. The annual loss due to BSR is estimated at PhP. 20 million equivalent to Rp3.5 billion. At present, there is no effective control method against BSR and, therefore, varietal improvement through breeding resistant germplasms is needed. The present study aimed to determine the combining ability and the extent of additive and non-additive genetic effects in corn inbred lines with a range of reaction to BSR. Four resistant lines (S3YB 137-1-1-B, TUPI (S3) 5-1-B, TUPI (S3) 15-2-B, and 97-835) and two susceptible lines (CML 295 and 97-733) were used as genetic materials. Generation of test entries and evaluation of disease resistance were conducted at the experimental farm station of University of the Philippines Los Banos and Institute of Plant Breeding Los Banos, respectively, during 2002 to 2003 wet seasons. Griffing’s diallel mating system Model 1, Method 1 was followed in generating the test entries to make a total of 36 entries (six selfed parental lines and 15 each of F1 crosses and their reciprocalcrosses). The entries were then evaluated for disease resistance in a yield trial following a randomized complete block design (RCBD) with two replications. Results of diallel analysisshowed two lines, S3YB 137-1-1-B and TUPI (S3) 5-1-B, exhibited the best general combining ability (GCA) for resistance to BSR, while the crosses S3YB 137-1-1-B x TUPI (S3) 5-1-B and TUPI (S3) 5-1-B x 97-835 performed the best specific combining ability (SCA) for the resistance. GCA effect was greater than that of SCA. This indicated that additive gene effects were found to be more important than non-additive gene effects in the expression of resistance to BSR in the six corn lines used. Therefore, breeding programs towards recurrent selection that emphasize GCA would be more appropriate forBSR resistance improvement involving those six lines.